A study of motivation and learning in Malaysian manufacturing industry. Issue 1 (1st January 2017) - Mat, Shafizal; Case, Keith; Mohamaddan, Shahrol; Goh, Yee Mey
Abstract: Problems of motivation and job satisfaction have continued to plague developing countries like Malaysia. The driving factors to motivate employees have frequently been studied, but no correlation between motivation and job satisfaction has been found. The study described here focuses on work motivation and satisfaction together with their relationships with learning behaviours. The main research consisted of an industrial study of 356 employees from manufacturing industries in Malaysia. The study revealed that unskilled employees preferred group working on complex tasks whereas skilled employees preferred to work individually, in both cases increasing motivation and satisfaction. Task complexity was found to be an important factor in job design and learning. Learning in groups was a significant factor in workplace learning for both unskilled and skilled employees. Knowledge of the relationships between motivation and learning is expected to be useful for employers and policy makers in organisations especially in manufacturing industries in Malaysia.